Chemical Composition, Antimicrobial and Antioxidant Activities of Essential Oils from Organically Cultivated Fennel Cultivars - Mahmoud A. Saleh; Faiza M. Hammouda; Fawzia H. Abdel-Rahman; Elsayed A. Omer; Saber F. Hendawy; Abeer Y. Ibrahim; Abdelaaty A. Shahat (Molecules, 2011)
Essential oils of the fruits of three organically grown cultivars of Egyptian fennel (Foeniculum vulgare var. azoricum, Foeniculum vulgare var. dulce and Foeniculum vulgare var. vulgare) were examined for their chemical constituents, antimicrobial and antioxidant activities. Gas chromatography/mass spectrometry analysis of the essential oils revealed the presence of 18 major monoterpenoids in all three cultivars but their percentage in each oil were greatly different. trans-Anethole, estragole, fenchone and limonene were highly abundant in all of the examined oils. Antioxidant activities of the essential oils were evaluated using the DPPH radical scavenging, lipid peroxidation and metal chelating assays. Essential oils from the azoricum and dulce cultivars were more effective antioxidants than that from the vulgare cultivar. Antimicrobial activities of each oil were measured against two species of fungi, two species of Gram negative and two species of Gram positive bacteria. All three cultivars showed similar antimicrobial activity.